Internationalization Strategy of Chinese E-Business Companies. Issue 4 (16th March 2018) - Huo, Da; Ouyang, Rihui
Abstract: The e-business market has experienced a speeding development at emerging market. This research aims to identify the corporate-level factors that influence decisions of pursuing an internationalization strategy at e-business companies from emerging market, based on the study of Chinese e-business companies. The Probit model and General Estimation Equation (GEE) estimation are performed to analyze the effect of corporate-level factors on the decisions of internationalization strategy, and the Heckman selection model is further performed to analyze the sample selection of Chinese e-business companies in their strategic decisions. This research will be helpful to managers and administrators of e-business companies from emerging market.